1995
DOI: 10.1111/j.1526-4610.1995.hed3502093.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Cysticercosis in Ecuador, South America

Abstract: Intractable headaches have been described as the presenting complaint of many patients with T. solium neurocysticercosis. We conducted a house-to-house neuroepidemiological survey of 2,723 residents of an Andean community, known to be endemic for this infection. Migraine headaches were confirmed in 187 cases (68.7 per thousand), and tension headaches were diagnosed in 77 cases (28.3 per thousand). Fifty-seven migraine sufferers accepted computed tomography examination, and in 19 it revealed neurocysticercosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 3 publications
3
37
0
3
Order By: Relevance
“…Nevertheless, recent studies from Brazil, Chile and Ecuador show that headache is highly prevalent in these countries and imposes a large economic burden on healthcare systems stretched to their limits. As in developed countries, migraine and chronic tension-type headache are the most common subtypes of headache disorders in South America [32][33][34][35][36]. Tekle Haimanot reported that "literature on prevalence and health burden in Africa is scanty" [37].…”
Section: Influence Of Race and Geographymentioning
confidence: 99%
“…Nevertheless, recent studies from Brazil, Chile and Ecuador show that headache is highly prevalent in these countries and imposes a large economic burden on healthcare systems stretched to their limits. As in developed countries, migraine and chronic tension-type headache are the most common subtypes of headache disorders in South America [32][33][34][35][36]. Tekle Haimanot reported that "literature on prevalence and health burden in Africa is scanty" [37].…”
Section: Influence Of Race and Geographymentioning
confidence: 99%
“…4 Much of the research on T. solium cysticercosis has focused on determining prevalence rates, assessing the accuracy of diagnostic methods, and comparing therapeutic regimens. [5][6][7] These investigations have established that neurocysticercosis has public health significance because of its medical and economic impact on both humans and livestock. Operational research is needed to define interventions to limit these parasites.…”
mentioning
confidence: 99%
“…Neurocysticercosis (NCC) is the most common parasitic disease of the human central nervous system (CNS) and is caused by the presence of Taenia solium metacestodes in the brain (19,57,72,74). Seizures are the most common clinical manifestation associated with NCC (20,73), and less common symptoms include headache, increased intracranial pressure, and altered mental state (18,20,60,65). CNS infection with Mesocestoides corti has been used as a model for NCC (12).…”
mentioning
confidence: 99%